Effects of medagogy-based health literacy enhancement on self-management behaviors and functional capacity among older persons with chronic heart failure: A randomized controlled trial - Saowaluk Thummak; Sirirat Panuthai; Rojanee Chintanawat; Nattaya Suwankruhasn (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Appropriate self-management behaviors and good functional capacity are crucial to reduce complications in older persons with chronic heart failure. Health literacy and transformative learning can be used in health education to motivate health behavior change, but limited research has examined their effects on health literacy for self-management behaviors and functional capacity in older persons with chronic heart failure. Objective: To investigate the effect of medagogy-based health literacy enhancement on self-management behaviors and functional capacity in older persons with chronic heart failure. Methods: This assessor and statistician-blinded, randomized controlled trial involved 70 older persons with chronic heart failure attending a heart clinic at a hospital in central Thailand. Permuted block randomization with a block size of four was employed to assign the participants to either the experimental group (n = 35) receiving a 5-session medagogy-based health literacy enhancement program over three weeks, or the control group (n = 35) receiving standard care. Outcomes were measured at baseline, 1 month post-intervention (self-management behavior), and 2 months post-intervention (functional capacity). Data analysis followed the intention-to-treat principle, using split-plot ANOVA and Repeated-Measures ANCOVA to adjust for imbalances in baseline functional capacity. Results: After the program, significant time and group interaction effects were found for self-management behavior (F(1,68) = 91.322, p < 0.001; ƞp2 = 0.573) and functional capacity (F(1, 67) = 5.424, p < 0.05; ƞp2 = 0.075). The experimental group demonstrated significantly higher mean scores for self-management behaviors than before the program (MD = 20.143, 95% CI = 17.561, 22.725; p < 0.001), and than the control group (MD = 18.686, 95% CI = 15.850, 21.521; p < 0.001). For functional capacity, the experimental group achieved a significant within-group improvement from baseline (p < 0.05) and a significantly higher adjusted mean capacity at post-intervention than the control group (Madj = 20.887, 95% CI = 2.986, 38.787; p < 0.05). Conclusion: The program led to improved short-term self-management behaviors and functional capacity. It can be used by nurses as a structured, patient-centered health education to promote older people’s self-management and functional capacity. However, multi-site and longitudinal follow-ups are recommended for future studies. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250908004)